Stressed-Strain State of Multi Layer Foil under One-Axis Tension; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Demidov V. N. Valery Nikolaevich (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen